2014
DOI: 10.3109/0142159x.2014.918256
|View full text |Cite
|
Sign up to set email alerts
|

Informed choice of entering medical school and academic success in Iranian medical students

Abstract: Idealistic views of medicine should be replaced by rational and logical ones to help students select the careers best suited to their abilities and talents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Unlike in some studies, conducted in Germany [ 46 ], Australia [ 47 ], Sri Lanka [ 48 ], and Iran [ 49 ], participants’ conception of academic success in the present study encompassed more than just academic grades (the simple traditional indicator); it also included skills related to the practice of medicine, such as mastery of medical knowledge, clinical skills and communication skills. This finding has several implications.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in some studies, conducted in Germany [ 46 ], Australia [ 47 ], Sri Lanka [ 48 ], and Iran [ 49 ], participants’ conception of academic success in the present study encompassed more than just academic grades (the simple traditional indicator); it also included skills related to the practice of medicine, such as mastery of medical knowledge, clinical skills and communication skills. This finding has several implications.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study conducted among medical students in Australia, Brazil, Iran. [43][44][45] The results of regression analysis indicated that having prior knowledge and positive experience in the medical school are statistically significant (p <0.05) predictor of both preclinical and 5th years cumulative GPA. This finding is consistent to one found in an Iranian study of medical students, which found that students who had made an informed choice of medicine had greater final year scores and satisfaction than those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent to one found in an Iranian study of medical students, which found that students who had made an informed choice of medicine had greater final year scores and satisfaction than those who had not. 44 According to research findings, satisfaction with a career in medicine would almost certainly result in a longer career and higher quality of care. Doing this can minimize dropout, disappointment, and negative attitudes towards medical education and career.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Farrokhi- Khajeh-Pasha et al (2014), who conducted a cross-sectional survey of 220 Iranian medical students from six schools to assess whether they made an informed choice when applying to medicine. Only 32.5% of respondents had made an informed choice to study medicine.…”
Section: An Uninformed Methodologymentioning
confidence: 99%